Pengaruh Leverage, Profitabilitas, Likuiditas dan Collateralizable Asset terhadap Kebijakan Dividen pada Perusahaan Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia (BEI) pada Tahun 2017 – 2022 - Sindi Trilia (AKUNTANSI 45, 2024)
This Analysis Aims To See The Influence Of Leverage, Profitability, Liquidity And Collateralizable Assets On Dividend Policy. The Analysis Was Carried Out In The Pharmaceutical Sub-Sector Manufacturing Industry Which Is Recorded On The Indonesia Stock Exchange (Bei) For The 2017-2022 Period. The Sampling Method Used Was Purposive Sampling, And Resulted In A Sample Of 9 Companies With 6 Years Of Observation, Resulting In 54 Research Samples. The Analysis Design In This Research Is To Apply A Multiple Linear Regression Analysis System. The Results Of This Analysis Show That Liquidity Has A Positive Effect On Dividend Policy, While Leverage, Profitability And Collateralizable Assets Have No Effect On Dividend Policy.